Research progress of HIF-1a on immunotherapy outcomes in immune vascular microenvironment - Shi, Shaoyan; Ou, Xuehai; Liu, Chao; Wen, Hao; Ke, Jiang (Frontiers in Immunology, 2025)
The hypoxia-inducible factor-1α (HIF-1α) plays a key role in facilitating the adaptation of cells to hypoxia, profoundly influencing the immune vascular microenvironment (IVM) and immunotherapy outcomes. HIF-1α-mediated tumor hypoxia drives angiogenesis, immune suppression, and extracellular matrix remodeling, creating an environment that promotes tumor progression and resistance to immunotherapies. HIF-1α regulates critical pathways, including the expression of vascular endothelial growth factor and immune checkpoint upregulation, leading to tumor-infiltrating lymphocyte dysfunction and recruitment of immunosuppressive cells like regulatory T cells and myeloid-derived suppressor cells. These alterations reduce the efficacy of checkpoint inhibitors and other immunotherapies. Recent studies highlight therapeutic strategies that target HIF-1α, such as the use of pharmacological inhibitors, gene editing techniques, and hypoxia-modulating treatments, which show promise in enhancing responses to immunotherapy. This review explores the molecular mechanisms of action of HIF-1α in IVM, its impact on immunotherapy resistance, as well as potential interventions, emphasizing the need for innovative approaches to circumvent hypoxia-driven immunosuppression in cancer therapy.